PERFORMANCE OF SUCKLING FROM BALI PIGS WITH GIVEN CHICKEN FARM WASTE CONCENTRATE - T. I. A. S., ARDANI; ARIANA, I. N. T.; OKA, A. A.; SUTAMA, I. N. S. (Majalah Ilmiah Peternakan; Vol 27 No 3 (2024): Vol. 27 No. 3 (2024), 2024)
The aim of the research was to determine the performance of suckling pigs from bali pigs has given fed concen- trate protein of chicken farm waste (KPLA). The research used a Completely Randomized Design (CRD) with three treatments and each treatment was repeated six times. The research used 18 bali pigs in the grower phase with an average weight of 13.30 ± 0.79 kg. The three treatments consisted of A: Ration without KPLA + 24% CP.152 (con- trol), B: Ration with 12% KPLA+12% CP.152, and C: Ration with 24% KPLA+0% CP.152. The variables observed were slaughter body weight, carcass weight, carcass percentage, suckling weight, suckling weight loss, and suck- ling pig color. The results of the research showed that giving 12% KPLA (treatment B) had no significant effect on slaughter body weight, carcass weight, carcass percentage, suckling weight, suckling weight loss and color of suc- kling bali pigs (P>0.05). The administration of 24% KPLA and 0% CP.152 (treatment C) resulted in a significant decrease in suckling weight and an increase in weight loss in bali pigs (P<0.05). The conclusion of this research is that by administering up to 24% KPLA (C) it can reduce the weight of the suckling bali pigs and increase the weight loss of the suckling bali pig.